Zarligaar togtooson gadaad Mongol, Hoton ajmgijn van güngüüdijn Iltgėl šastir, 79-120-r dėvtėr = Peerage Succession's Tables and Biographies of Vassal Mongol and Uigur Princes and Dukes compiled by Imperial Order : Chapter LXXIX-CXX = ǰarliġ-iyar toġtaġa-son ġadaġadu mongġol, qotung, aimaġ-un vang günggüd-ün iledkel šastir - Cėrėndorž, Cėgmėdijn; Ėrdėnėbold, Lchagvasurėngijn; Baržav, Doržijn; Ganbat, Njamdagijn (Bit Press, 2009)
Cyrillic transliteration and commentary of a Mongolian script document providing succession and biographical information on vassal Mongolian and Uighur nobility